Efektivitas Gamifikasi Pembelajaran Melalui Blooket untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran TIK Kelas VIII-A di SMP Al-Ihya Cihaur - Awaliyah, Fitri; Mahpudin, Asep (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study was to determine the significant difference in students’ learning outcomes before and after the implementation of learning gamification through Blooket.This research is a quantitative study using a Pre-Experimental Design with the One Group Pretest-Posttest Design model. The sampling technique employed in this study was a census/total sampling method. The study involved 18 students from class VIII A at SMP Al-Ihya Cihaur. The data collection technique used was testing. The research instruments consisted of pre-test and post-test questions. The data analysis techniques used in this study included descriptive analysis, normality test, and t-test. Based on the research findings, there was a difference in students' learning outcomes before and after the treatment. The results of the hypothesis test showed that the average post-treatment score in the experimental group reached 78,95, while the pre-treatment score was 50,53. Thus, there was a difference of 28,42 points, indicating a higher improvement in the post-treatment scores. The t-test resulted in a significance value of p = 0.000, which is less than 0.05. This indicates a significant difference between the scores before and after the treatment. Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted